2018
DOI: 10.1088/1361-6463/aaa1af
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of magnetoimpedance effect in Co-based ribbon by laser patterning for sensor arrays application

Abstract: The giant magnetoimpedance (GMI) effect in Co-based ribbon with different patterning structures, named series structure (SS), parallel structure (PS) and cross structure (CS) with different angle, has been investigated. Absolute variation of impedance and GMI ratio (154% for sample SS, 220% for sample PS and 236% for sample CS at 5 MHz) in different patterning structures have been evaluated comprehensively. The double-peak GMI curves with a spindle-shape embossment are observed in sample PS and CS, which could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…FeCoSiB amorphous alloys can be produced by sputtering, single-roller, rotatingwater quenching (Figure 25), rained growth, and stress annealing methods (Liang et al, 2020, Zhao et al, 2018, Sarkar et al, 2013 and find technological applications as distribution transformers, anti-theft tags, motors, high frequency inductors, sensors and actuators.…”
Section: Fecosibmentioning
confidence: 99%
“…FeCoSiB amorphous alloys can be produced by sputtering, single-roller, rotatingwater quenching (Figure 25), rained growth, and stress annealing methods (Liang et al, 2020, Zhao et al, 2018, Sarkar et al, 2013 and find technological applications as distribution transformers, anti-theft tags, motors, high frequency inductors, sensors and actuators.…”
Section: Fecosibmentioning
confidence: 99%
“…However, when the dc magnetic field is applied perpendicular to the main axis, it is interesting to found that the GMI curve of NFCFCFN laminate shows an unusual single peak instead of typical double peaks [7][8][9][10][11][12][13][14][15]29] during either increasing or decreasing branch (shown as figure 4(b)).…”
Section: Gmi Effect Of Magnetic Heterostructurementioning
confidence: 99%
“…In this study, we propose an alternative logic-in-memory device based on the improved asymmetric and hysteretic giant magnetoimpedance (GMI) effect of a magnetic heterostructure for the first time. For the GMI effect, the electrical impedance of a ferromagnetic conductor usually varies with the external dc magnetic field due to the varying magnetic permeability, which has attracted intense interest due to applications at the sensitive magnetic sensor [7][8][9]. The GMI effect of soft magnetic material usually varies nonlinearly and symmetrically near zero fields [7][8][9], which is inconvenient for obtaining the proper signal and determining the magnetic field direction for the magnetic sensor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This very good GFA of Co-based alloys allows different shape samples to be developed for research. As described above, the researchers were working on bulk metallic glasses (BMG) rods made using the copper mold injection casting method, but researchers also successfully obtained ribbons by melt spinning processes [ 22 , 23 ]. A more interesting shape, which was also studied in this work, is the powder form of an amorphous Co-based alloy.…”
Section: Introductionmentioning
confidence: 99%